Peran Ekonomi Islam Dalam Pembangunan Ekonomi Nasional Yang Berkelanjutan di Era Society 5.0 - Tira Aprilia; Ratih Meisda Sari; Robiatul Adawiyah; Dian Efrilia; Levania Anggesta; Tri Lulu Handayani (Journal of Economics and Business, 2024)
ABSTRAK Islamic economics offers a framework based on the values of justice, balance, and sustainability, which is a solution for sustainability-oriented national economic development. This article examines the main contributions of Islamic economics through the approach of Islamic financial systems, wealth redistribution based on zakat, infaq and waqf (ZISWAF), and the application of justice and ethical principles in economic activities. This research uses a descriptive-analytical method with secondary data to explain how the implementation of Islamic economics can support sustainable development goals. The results of the study show that the principles of Islamic economics make a significant contribution in creating economic equity, supporting environmental sustainability, and improving financial stability and inclusion.   ABSTRAK Ekonomi Islam menawarkan kerangka kerja yang berbasis pada nilai-nilai keadilan, keseimbangan, dan keberlanjutan, yang menjadi solusi bagi pembangunan ekonomi nasional yang berorientasi pada keberlanjutan. Artikel ini mengkaji kontribusi utama ekonomi Islam melalui pendekatan sistem keuangan syariah, redistribusi kekayaan berbasis zakat, infaq, dan wakaf (ZISWAF), serta penerapan prinsip keadilan dan etika dalam kegiatan ekonomi. Penelitian ini menggunakan metode deskriptif-analitis dengan data sekunder untuk menjelaskan bagaimana implementasi ekonomi Islam dapat mendukung tujuan pembangunan berkelanjutan. Hasil kajian menunjukkan bahwa prinsip-prinsip ekonomi Islam memberikan kontribusi signifikan dalam menciptakan pemerataan ekonomi, mendukung keberlanjutan lingkungan, serta meningkatkan stabilitas dan inklusi keuangan. .